Towards a software framework for reconfigurable and adaptive fixturing systems - Ryll, Marco (2011)
There is an ongoing trend towards advanced fixturing systems that can be automatically reconfigured for different workpieces and dynamically adapt the clamping forces during the manufacturing process. However, the increased utilisation of computer technology and sensor feedback currently requires a significant amount of programming effort during the development phase and deployment of such fixtures which impairs their successful industrial realisation.